Phosphorylation of the Hepatitis B Virus Large Envelope Protein - Fogeron, Marie-Laure; Lecoq, Lauriane; Cole, Laura; Montserret, Roland; David, Guillaume; Page, Adeline; Delolme, Frédéric; Nassal, Michael; Böckmann, Anja (Frontiers in Molecular Biosciences, 2022)
We here establish phosphorylation sites in the human hepatitis B virus (HBV) large envelope protein (L). L is involved in several functionally important interactions in the viral life cycle, including with the HBV cellular receptor, the HBV capsid, the Hsc70 chaperone, and cellular membranes during fusion. We have recently shown that cell-free synthesis of the homologous L protein of duck HBV (DHBV) in wheat germ extract results in very similar phosphorylation events to those previously observed in animal cells. We here report the human HBV L protein phosphorylation sites as established in vitro using cell-free synthesis, mass spectrometry and NMR. While in the avian virus phosphorylation of L has been shown to be dispensable for infectivity, the identified locations in the human virus protein, both in the PreS1 and PreS2 domains, raise the intriguing possibility that they might play a functional role, since they are found at strategic sites predicted to be involved in L interactions. This would warrant further investigation of a possible function in virion formation or cell entry.